Economic reforms and technological development - Giriappa, S. (Delhi : Daya Pub. House, 1998)
Papers presented at National Seminar on the "Impact of Economic Refo rms on Science and Technology", held at Mangalore on February 24-25, 19 97.
Includes bibliographical references and index.
Keywords: Technology -- India; India -- Economic policy -- 1991-